2013
DOI: 10.1371/journal.pone.0053902
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Aromatase CYP19 rs10046 Polymorphism and Breast Cancer Risk: From a Case-Control to a Meta-Analysis of 20,098 Subjects

Abstract: Lifetime exposure to estrogen is a factor that plays an important role in the pathogenesis and progression of breast cancer. Genetic variants in genes of the biosynthesis and metabolism of estrogen have been associated with breast cancer risk. Among them, the CYP19 gene encodes for aromatase, the enzyme that catalyzes the conversion of androgens to estrogens. The rs10046 polymorphism on the CYP19 gene has been related to levels of circulating estradiol and to the estradiol/testosterone ratio. To date, epidemio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 42 publications
3
16
0
2
Order By: Relevance
“…A Chinese study provided evidence that the CYP19 rs10046 polymorphism is associated with breast cancer risk among Chinese women [25] and results from a study in a Spanish population also revealed an association between rs10046 and breast cancer risk. In this study, the carriers of at least one C allele had an increased risk of developing breast cancer [26], which is in agreement with other studies, where the frequency of the C allele is higher in cases vs. controls [12,19]. In contrast, Kristensen et al .…”
Section: Resultssupporting
confidence: 92%
“…A Chinese study provided evidence that the CYP19 rs10046 polymorphism is associated with breast cancer risk among Chinese women [25] and results from a study in a Spanish population also revealed an association between rs10046 and breast cancer risk. In this study, the carriers of at least one C allele had an increased risk of developing breast cancer [26], which is in agreement with other studies, where the frequency of the C allele is higher in cases vs. controls [12,19]. In contrast, Kristensen et al .…”
Section: Resultssupporting
confidence: 92%
“…Circulating estrogen levels were higher among women with 7 base repeat alleles in our study [46] as in most other studies [34], [47]. However, despite the relationship between these SNPs and estrogen levels, most studies, including our own, have not observed any association between these SNPs in CYP19 and UGT1A1 and breast cancer risk [32], [48].…”
Section: Discussionsupporting
confidence: 57%
“…Association analysis between rs10046 and BC in different populations showed inconsistent results (Zhang et al, 2009;Pineda et al, 2013). Karin et al (Zins et al, 2014) reported that the TT genotype of this polymorphism was associated with an increased BC risk.…”
Section: Discussionmentioning
confidence: 99%